Ensaios de adubação nitrogenada e fosfatada da cultura do feijão (Phaseolus vulgaris L), na zona metalúrgica de Minas Gerais - Bolsanello, Juarez; Vieira , Clibas; Sediyama, Carlos S; Alves Vieira , Hélio (Revista Ceres, 2025)
Five trials of nitrogen and phosphate fertilizers in dry bean culture (Phaseolus vulgaris L.) were conducted in three localities of the Zona Metalúrgica of Minas Gerais, Brazil: Itaúna (two experiments), Pará de Minas (two experiments) and Divinópolis.